2015
DOI: 10.1371/journal.pone.0124006
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis Isolates from Patients with Irritable Bowel Syndrome and from Asymptomatic Carriers Exhibit Similar Parasitological Loads, but Significantly Different Generation Times and Genetic Variability across Multiple Subtypes

Abstract: Blastocystis spp is a common intestinal parasite of humans and animals that has been associated to the etiology of irritable bowel syndrome (IBS); however, some studies have not found this association. Furthermore, many biological features of Blastocystis are little known. The objective of present study was to assess the generation times of Blastocystis cultures, from IBS patients and from asymptomatic carriers. A total of 100 isolates were obtained from 50 IBS patients and from 50 asymptomatic carriers. Up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 58 publications
4
24
1
Order By: Relevance
“…For Blastocystis, greater diversity was found in the Caribbean region in the departments of Bolívar and Córdoba. This was expected since Blastocystis usually has high inter-subtype variability , as reported in a study of SSU DNAr genes conducted in Mexico, where the results showed similar diversity indices within each subtype, despite their different geographical regions and different inter-subtype indices (Villegas-Gómez et al, 2016), and a greater diversity between the STs of a control group compared with one associated with irritable bowel syndrome (Vargas-Sanchez et al, 2015). Like G. intestinalis, the number of sequences for Córdoba was very small, avoiding any strong conclusions regarding this population.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…For Blastocystis, greater diversity was found in the Caribbean region in the departments of Bolívar and Córdoba. This was expected since Blastocystis usually has high inter-subtype variability , as reported in a study of SSU DNAr genes conducted in Mexico, where the results showed similar diversity indices within each subtype, despite their different geographical regions and different inter-subtype indices (Villegas-Gómez et al, 2016), and a greater diversity between the STs of a control group compared with one associated with irritable bowel syndrome (Vargas-Sanchez et al, 2015). Like G. intestinalis, the number of sequences for Córdoba was very small, avoiding any strong conclusions regarding this population.…”
Section: Discussionsupporting
confidence: 61%
“…This is because there is a great diversity of fauna and ecosystems in the country. For instance, in the Caribbean and Orinoco regions exist diverse ecosystems including savannah, mountainous forest, bodies of water, jungles and moorland (Barón, 2002;IDEAM et al, 2007;Vergara, 2018), these are exploited by each department to generate economic resources, and the presence there of nonhuman primates, rodents, birds and pigs infected with intestinal protozoa could increase the risk of zoonotic transmission in rural areas as has been reported in the country and in Brazil (Rondón et al, 2017;Valença-Barbosa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, in another study performed in similar populations of these howler monkeys, 68% of these animals were infected with Blastocystis ST8, while humans living in close proximity were infected with ST1, ST2 and ST3 [15]. Interestingly, although these subtypes (ST1-ST3) are distributed worldwide, they are common in America [8, 40, 41]. In the present study, 39% and 38% of A .…”
Section: Discussionsupporting
confidence: 48%
“…Genetic diversity analyses within and between populations were performed using DnaSPv4 [39], and indices, such as nucleotide diversity (π), haplotype polymorphism (θ), gene flow ( Nm ),genetic differentiation index (F ST ) and Tajima’s D test were obtained. These indices have been previously applied for population genetics studies in Blastocystis [40, 41]. They denote the average proportion of nucleotide differences between all possible pairs of sequences in the sample (π); the proportion of nucleotide sites expected to be polymorphic in any suitable sample from this region of the genome (θ); the movement of organisms among subpopulations ( Nm ); and the differentiation between or among populations (F ST ).…”
Section: Methodsmentioning
confidence: 99%
“…The geographic distribution of the identified subtypes in human might be affected by different factors such as region, weather, contact with reservoir hosts, cultural behaviors and transmission route (1). Among identified nine subtypes in humans, the most common are STs 1 -4 with approximately 90% of human infections (12), which their prevalence is vary from one country to another (13). Subtype 3 is the most common ST with a cosmopolitan distribution, but ST4 is restricted to European countries and being rare in North Africa, the Middle East, and South America (5).…”
Section: Introductionmentioning
confidence: 99%